Mapping of domain structure in Barium Titanate single crystals by synchrotron X-ray topography - Potnis, P; Huber, J; Sutter, J; Hofmann, F; Abbey, B; Korsunsky, A (2010)
Imaging of domains is a key step in understanding the microstructure and hence the properties of ferroelectric single crystals. This understanding is essential for exploiting engineered domain configurations to achieve enhanced performance. In this paper, single crystals of Barium Titanate are observed by reflection topography using unfocussed monochromatic synchrotron X-ray light. A 10 x 10 mm polished surface of an unpoled crystal was mapped to form a composite image, indicating a fine structure of a- and c-domains. By making use of the angular separation of the diffracted reflections and specimen rocking, the relative tilts between adjacent domains about two orthogonal axes were found. Angular resolution better than 0.1mrad in tilt measurements allowed the local elastic curvature of lattice planes to be observed. The resulting composite images show well defined boundaries between regions of distinct microstructure, and give an indication of the proportion of the domain types present. Over large regions of the crystal the domain structure was finer than the X-ray camera resolution of 6.5μm; AFM and SEM imaging of domains was then used to confirm the typical domain spacing. The results are interpreted in the context of models of compatible microstructure in tetragonal crystals using microscopy of etched crystals to assist the interpretation. The technique shows promise for mapping fine microstructure in single crystals, through the use of high resolution X-ray cameras, and is successful in revealing lattice orientation information that is not normally available in optical or AFM measurements. © 2010 Copyright SPIE - The International Society for Optical Engineering.